Quaestiones Geographicae: Five decades of geographical excellence - Kostrzewski, Andrzej; Dominiak, Joanna; Zwoliński, Zbigniew; Rzodkiewicz, Monika; Stachowiak, Krzysztof; Stryjakiewicz, Tadeusz (Quaestiones Geographicae, 2024)
The journal Quaestiones Geographicae, founded by Professor Stefan Kozarski in 1974, has played a key role in the development of geography and related sciences for five decades, promoting both Polish and international scientific research. Initially focused on physical geography, it evolved towards interdisciplinarity, encompassing a broad range of themes within the geographical sciences. Through its collaboration with the Sciendo platform and adoption of the Open Access model, the journal has expanded its international reach, attracting authors from over 40 countries and achieving an Impact Factor of 1 in 2023. Its most influential publications have explored statistical methods, geodiversity, and geomorphological heritage, highlighting the journal’s interdisciplinary character. The 50th anniversary is an opportunity to reflect on its contribution to the advancement of geography and to set new goals in addressing global challenges such as environmental crises, urbanisation, and digital technology development. Quaestiones Geographicae remains an invaluable platform for knowledge exchange, inspiring future researchers and supporting sustainable development at local and global levels.